2022
DOI: 10.1101/2022.12.19.521070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LRRK2 Kinase Activity Regulates Parkinson’s Disease-Relevant Lipids at the Lysosome

Abstract: Lysosomal dysfunction is a hallmark of Parkinson's disease (PD), and variants in several PD-associated genes, including LRRK2, perturb lysosomal homeostasis. Based on this, LRRK2 kinase inhibition is being explored as a therapeutic approach for the treatment of PD. LRRK2 inhibitors reduce levels of BMP, an endolysosomal lipid involved in glycosphingolipid (GSL) catabolism, in urine from preclinical models and clinical subjects, however, the mechanisms by which LRRK2 regulates BMP and the functional significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Depletion of LRRK2 and inhibition of LRRK2 kinase activity both enhance lysosomal proteolytic activity and increase the expression of multiple lysosomal hydrolases ( 32 ). Other work has revealed that LRRK2 kinase activity controls PD relevant lipids such as bis(monoacylglycerol)phosphates as well as glycosphingolipids at the lysosome ( 33, 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of LRRK2 and inhibition of LRRK2 kinase activity both enhance lysosomal proteolytic activity and increase the expression of multiple lysosomal hydrolases ( 32 ). Other work has revealed that LRRK2 kinase activity controls PD relevant lipids such as bis(monoacylglycerol)phosphates as well as glycosphingolipids at the lysosome ( 33, 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that pathogenic LRRK2 mutations cause kinase hyperactivity [ 18 ], and studies suggest that these mutations are associated with lysosomal swelling and dysfunction [ 19 , 20 ] A specific mechanism linking kinase hyperactivity with this cellular phenotype is suggested by molecular screens showing that LRRK2's primary function is to phosphorylate many of the family of Rab proteins [ 21 ], which are GTPases that act as effectors in membrane trafficking [ 22 ]. Rab8 and Rab10 are the main Rabs hyperphosphorylated by LRRK2 mutations [ 18 ], and both Rabs are recruited to damaged lysosomes [ 23 , 24 ].…”
Section: Autosomal-dominant Parkinson's Disease and The Endo-lysosoma...mentioning
confidence: 99%
“…Depletion of LRRK2 and inhibition of LRRK2 kinase activity both enhance lysosomal proteolytic activity and increase the expression of multiple lysosomal hydrolases ( 33 ). Other work has revealed that LRRK2 kinase activity controls PD relevant lipids such as bis(monoacylglycerol)phosphates as well as glycosphingolipids at the lysosome ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%